Do managers of South African manufacturing firms make optimal capital investment decisions? - E. Gilbert (South African Journal of Business Management, 2003)
Managing the deployment of a firm's assets in the form of capital goods is a vital determinant of a firm's ability to successfully compete over time. Corporate finance theory clearly prescribes a rule to ensure the optimality of these decisions: all capital investment decisions should be evaluated through the use of the net present value (NPV) rule while project specific risk should be incorporated through the adjustment of the discount rate used in the NPV analysis.This paper presents the results of a survey of the capital investment evaluation practices of South African manufacturing firms. The results indicate that the majority of firms surveyed do not use the NPV evaluation technique when making their capital investment decisions. Furthermore, those firms that do use this technique use it in combination with other, theoretically deficient (and redundant) techniques. Finally, they do not adjust for project specific risk as prescribed.
Keywords: 650